Minhaj Al-Da’wah Mush’ab Bin Umair Fi Da’watihi ‘Inda Ahli Yatsrib (Al-Madinah Al-Munawwarah) - Nurul Syuhada; Husnul Khatimah (Rayah Al-Islam, 2022)
ملخص البحث الدعوة هي وسيلة للرسل والأنبياء والعلماء بل واجبة على كل مسلم في تبليغ رسالة الإسلام لدعوة الناس إلى تطبيق مظاهر الإسلام ومضامن ما يشمل عنه من عدة جوانب الحياة. كما فعل مصعب بن عمير أول داع للإسلام في يثرب (المدينة المنورة) الذي بعثه النبي ﷺ إليهم قبل قدومه ﷺ إلى المدينة المنورة. وهدف للكتابة هذا البحث لمعرفة منهج الدعوة الذي استخدمه مصعب بن عمير في دعوته وكذا لتسهيل مسلم في إقامة دعوته. وتعتمد الباحثة لإنجاز كتابة هذا البحث باستخدام منهج المطالعة بعض الكتب الذي يثاق بها العلماء والأمة الإسلامية عامة لإقناء قارئ هذا البحث. فنتائج البحث عن منهج الدعوة مصعب بن عمير عند أهل يثرب هي منهج التلقى ومنهج الأخلاقى وكذا منهج العملية Abstract Da'wah is a means for the apostles, prophets and scholars and even the obligation of every Muslim to deliver the message of Islam to invite people to apply the conception and systemization of Islam from various aspects of life. As was done by Musab bin Umair in Islam the first city of Medina who was sent by the Prophet sallallaahu Alaihi wasallam before his arrival in the city of Medina. The aim of this paper is to find out how the method of Musab ibn Umair makes Da’wah easier for muslim in carrying out the activities of Da'wah. To discuss this topic, the authors chose to use the literature study method with a qualitative approach. Based on the results of the discussion, the method used by Musab ibn Umair in inviting residents of Medina to Islam was interpersonal, moral communication and apply the knowledge that has been learned .